Pengaruh Edukasi Kesehatan terhadap Peningkatan Pengetahuan Pengelolaan Sampah Sebagai Upaya Mewujudkan Program Bantul Bersih Sampah 2025 - Isni, Khoiriyah; Mustanginah, Tri (UI Scholars Hub, 2023)
Background. Indonesia's annual waste generation reaches 19,255,966.82 tons and daily waste of 52,756.07 tons in 2022. The population who live in Bantul is around one million people so that the waste generated by the community is 600 tons/day. While the Government of Bantul Regency can only accommodate 100 tons/day. Therefore, the government of Bantul Regency launched the Program of Bantul Bersih Sampah (Bantul Bersama) 2025. This program is community-based, so the main target must be involved first. However, the understanding of the people of Bantul regarding waste management is still low. Aim. The purpose of this study was to determine the effect of health education on increasing knowledge about waste management in order to realize the Clean Waste Bantul 2025. Method. This study is a a quasi-experimental. Respondents are housewives who are members of the dasa homestead group from three hamlets in Bantul Regency. Primary data collection was carried out using pre-test and post-test questionnaires regarding waste management. Data were analyzed using the Wilcoxon test to determine the effect of health interventions given to respondents. Result. Of the 41 housewives who participated in health education activities, only 26 respondents completed the pre-test and post-test questionnaires. The Wilcoxon test results significantly increased knowledge of waste management through health education (p-value> 0.05). Intervention in health education is one of the efforts to realize the 2025 Clean Garbage Bantul program, marked by increased public knowledge.